Meningkatkan Hasil Belajar Akidah Akhlak Melalui Metode Mind Mapping pada Siswa Kelas IV MI Muhammadiyah 02 Mariyai - Khotimah, Khusnul; Suharmoko, Suharmoko; Bunyamin, Bunyamin (Tarbiyah STAIN Sorong, 2017)
This Classroom Action Research was conducted at MI Muhammadiyah 02 Mariyai with the aim of improving student moral learning outcomes through the mind mapping method. The research subjects were grade IV students, amounting to 26 people. Researchers used two cycles, each of which consisted of three meetings. Data retrieval is done using learning outcomes tests and observation sheets. The collected data were analyzed both quantitative and qualitative data. Quantitative data is calculated using data analysis on Microsoft Excel. The results obtained showed an increase in moral learning outcomes ie from the average score of the initial ability of students 63.85 in the low category, then in the first cycle the average score of student learning outcomes increased to 76.35 in the medium category, and in the cycle, II increased to 86.15 which is in the high category. Increasing the score of student learning outcomes is also directly proportional to mastery learning. In the initial ability score, the number of students who finished learning was 8 people (30.77%), then in the first cycle increased to 16 people (61.54%), and in the second cycle increased again to 24 people (92.31%). Based on the results of this study, it can be concluded that an increase in the learning outcomes of the Moral Law in Class IV MI Muhammadiyah 02 Mariyai Students after using the mind mapping method.